2022
DOI: 10.3389/fonc.2022.881024
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Thyroid Peroxidase Antibody Predicts Recurrence in Papillary Thyroid Carcinoma: A Consecutive Study With 5,770 Cases

Abstract: BackgroundThyroid autoimmunity is common in papillary thyroid carcinoma (PTC) and was believed to confer a better prognosis; however, controversy still remains. This study aimed to investigate the prognostic value of chronic lymphocytic thyroiditis (CLT) and preoperative thyroid peroxidase antibody (TPOAb) in PTC patients.MethodsA retrospective analysis was performed on 5,770 PTC patients who underwent surgical treatment with pathologically confirmed PTC in our institution between 2012 to 2016. The patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…We initially observed that TPOAb+ DTC patients are more likely to exhibit bilateral and multifocal tumors. However, Wang’s study ( 47 ) with a considerably higher weight share in both results had a significant influence. Upon exclusion of the Wang’s study, we found no significant association between TPOAb and DTC multifocality (OR=0.91 [95% CI: 0.56–1.48], p=0.70) and bilaterality (OR=1.41 [95% CI: 0.74–2.66], p=0.29).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…We initially observed that TPOAb+ DTC patients are more likely to exhibit bilateral and multifocal tumors. However, Wang’s study ( 47 ) with a considerably higher weight share in both results had a significant influence. Upon exclusion of the Wang’s study, we found no significant association between TPOAb and DTC multifocality (OR=0.91 [95% CI: 0.56–1.48], p=0.70) and bilaterality (OR=1.41 [95% CI: 0.74–2.66], p=0.29).…”
Section: Discussionmentioning
confidence: 78%
“…Our analysis focused on five studies ( 40 , 42 , 44 , 46 , 47 ) to determine whether the risk of extrathyroidal extension differs among DTC patients with various TPOAb levels. Among the 1804 TPOAb+ and 7168 TPOAb– patients, little difference in the risk of extrathyroidal extension was found, 12% and 11%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Low TPOAb level is found to be one of the signi cant risk factors of central lymph node metastasis [16,23] . While some studies have shown the opposite result, high TPOAb level (> 100 IU/mL) is an independent risk factor for LNM in PTC [24,25] . Further studies on the effects of TPOAb on LNM and its underlying biological mechanisms are needed.…”
Section: Discussionmentioning
confidence: 82%